Agricultural Credit Supply in Developing Eight Organization’s Member Countries: The Behavior Towards Agricultural Risk - Wulandari, Ries; Siregar, Hermanto; Firdaus, Muhammad; Beik, Irfan Syauqi (Universitas Panji Sakti, 2024)
The 11th Global Food Security Index (2022) shows an increase in agriculture risk and a decline in the food environment for the third year which is feared to threaten global food security. It is urgent to have more concern for food security in advanced and emerging economies, such as Developing Eight (D-8) economies. This paper analyzes the determinants of agriculture credit supply in D-8’s banking and how they affect agriculture risk. The study uses panel quarterly time series data from 2013Q01-2022Q04 and cross-section data from 7 countries as members of the Developing Eight (D8) Organization. This study employs the dynamic panel analysis, Panel Autoregressive Distributed Lag (PARDL) - Pooled Mean Group (PMG) approach. The result shows that agriculture credit supply and its explanatory variables have a significant relationship in the long run. Unfortunately, only previous credit supply and agriculture risk contribute to the agriculture credit supply in the short run. The result varies across countries in the short run. Banking in Indonesia considers agricultural risk by decreasing the agricultural credit supply while banking in Malaysia and Turkey maintains a positive agricultural credit supply despite the increase in agricultural risk.